Efikasi Herbisida Metil Metsulfuron Terhadap Gulma pada Pertanaman Kelapa Sawit (Elaesis guinensis Jacq.) yang Belum Menghasilkan (TBM - Khasanah, Nurul Hidayati; Sriyani, Nanik; Evizal, Rusdi (Jurnal Penelitian Pertanian Terapan, 2015)
The objectives of this research were to find out the efficacy of metsulfuron methyl herbicide to weeds of unproductive yet oil palm, to find out the growing weeds composition change after application, and to findout the influence. This research was conducted in randomizedgroup design with 8 treatments of metsulfuron methyl dosages of 15, 20, 25, 40, and 50 h.ha-1, mechanical weeds removal, with control, and 4 repetitions. Variance homogeneity was tested with Bartlett test and data addition was tested with Tukey test. Differences in median tested using Least Significant Differenc (LSD) level 5%. The results showed that: (1) 15 to 50g.ha-1 metsulfuron methyl dosages were effective to oppress total weed scovering, total weeds toxicity anwide leaf weeds dry weight12 weeks after application (WAA), grass type weeds dry weight at particular dosages to 4 (WAA) and dry weight of dominant weeds including Cynodon dactylon, Commelina benghalensis and Centro semapubescens; (2) various dosages to test caused composition changes of weeds types in observation 2 to 12 (WAA); (3) weeds controlling in various dosages to test did not poison leafs and roots of unproductive yet oil palm. Keywords: Metsulfuron methyl, weeds, unproductive yet oil palm.